2019
DOI: 10.1002/brb3.1369
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐33 as a novel marker for long‐term prognosis and recurrence in acute ischemic stroke patients

Abstract: Objectives Interleukin‐33, a newly identified member of interleukin‐1 family, had been confirmed to play a crucial role in regulating inflammatory responses in various disease. However, the exact role of interleukin‐33 in the disease process of acute ischemic stroke still remains unclear. This study aims to demonstrate the relationship between interleukin‐33 levels and long‐term functional outcome as well as ischemic stroke recurrence. Methods Three hundred and four first‐ever acute ischemic stroke patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…Therefore, activated glial cellular signaling enhances the expression of M2 polarization markers on microglia and impairs the expression of M1 polarization markers after tMCAO. A clinical study of 259 stroke patients demonstrated that higher interleukin‐33 levels are positively correlated with better prognosis . However, this conclusion was inconsistent with the findings of another clinical study on 175 patients with aneurysmal subarachnoid hemorrhage (aSAH); this study reported that increases in the level of serum IL‐33 predict a worse prognosis of aSAH .…”
Section: Microglia‐neighboring Cells Crosstalk and Interventions For mentioning
confidence: 78%
“…Therefore, activated glial cellular signaling enhances the expression of M2 polarization markers on microglia and impairs the expression of M1 polarization markers after tMCAO. A clinical study of 259 stroke patients demonstrated that higher interleukin‐33 levels are positively correlated with better prognosis . However, this conclusion was inconsistent with the findings of another clinical study on 175 patients with aneurysmal subarachnoid hemorrhage (aSAH); this study reported that increases in the level of serum IL‐33 predict a worse prognosis of aSAH .…”
Section: Microglia‐neighboring Cells Crosstalk and Interventions For mentioning
confidence: 78%
“…Higher serum IL-33 levels in acute ischemic stroke patients correlated positively with better prognosis, as compared with those with lower IL-33 levels. These patients presented with poorer outcome [85] suggesting that IL-33 is protective to stroke.…”
Section: Il-33mentioning
confidence: 98%
“…It is very attractive to find early serum markers to predict stroke recurrence. Different variables, such as IL-6 [43], IL-33 [44], VCAM-1 [15], CRP [45], vitamin D [46], and copeptin [47], had been proposed as useful biomarkers for predicting stroke recurrence events in patients with ischemic stroke. Similarly, we also found that CRP and IL-6 were independent predictor biomarkers for stroke recurrence.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%